The right to health and the principle of individual security - Gonzales Ojeda, Magdiel (2022)
The social and democratic rule of law is the answer to the standards of the modernity. In this new kind of State, principles and values have a new conception. On the one hand, such principles and values define and sustain the «design of State policy»; and, on the other, they establish the objectives that society intends to achieve for its full realization. These objectives are synthesized in the concept of the «social model», where not only life is effectively guaranteed, but also the total validity of fundamental rights, including the right to health. In the context of the social and democratic rule of law, security as an informing principle of the State assumes a greater content, which is aimed at achieving greater effectiveness of fundamental rights. From this inescapable requirement of the State, the obligation to guarantee true certainty in all activities in the lives of human beings currently constitutes the core of the principle of individual security.